Factors Influencing The Demand For Credit By The Private Sector In Kenya - Sarah Chebet; Peter W Muriu (European Scientific Journal, ESJ, 2016)
This study investigates the effects of selected macroeconomic variables on the Demand for credit by the private sector in Kenya. The study used annual time series data for the period 1980-2012. Data was obtained from Kenya National Bureau of Statistics, World Development Indicators and supplemented by Central Bank of Kenya. Using Vector Error Correction Model (VECM) methodology, the study established that; Public investment, Short term interest rate, Long term interest rate, Employment and Domestic debt have a positive effect on demand for credit by the private sector, while per capita GDP and Exchange rate have a negative effect. The policy implication of these results is that providing sound economic growth policies, a stable macroeconomic situation, policies leading to lower credit cost and greater financial liberalization would simultaneously boost lending and lower the risk of lending to the private sector.